Transformational Leadership in Government Organizations: The Role of Team Empowerment and Organizational Climate - Robiyati Podungge; Margono Setiawan; Achmad Sudiro; Mintarti Rahayu (AIBPM Publisher, 2022)
This study aims to analyze the effect of transformational leadership on employee performance and how this influence is mediated by team empowerment and organizational climate. Previous studies that examined transformational leadership were more focused on business organizations and were very limited to public organizations, especially government organizations. The research approach used is quantitative with descriptive analysis method. This research was conducted on 252 employees at the Education office in Gorontalo Province through questionnaires and open interviews. The results obtained in this study contain information about that within the organization a collaboration is needed in completing work with tasks and functions, so that superiors and subordinates do not only have a relationship as superiors and subordinates but as team work in completing work. In this case, transformational leadership in improving employee performance depends on a leader who leads them not only based on relationships in the organizational structure which will have an impact on non-optimal work results. The ability of a transformational leader is different from other types of leadership, transformational leadership in assigning tasks and work to not only based on orders, but behaving well with firmness to subordinates and embracing them as friends or friends.Â Keywords: Transformational Leadership, Team Empowerment, Organizational Climate, Employee Performance.